Morphology, crystal structure and adsorption performance of hydrothermally synthesized titania and titanate nanostructures - Lim, Linda Ying Wen (2012)
Titania (TiO2) and sodium titanate nanostructures with controllable phases and morphologies were synthesized by hydrothermal method with titanium disulfide (TiS2) as the starting material. Sodium 5 titanate nanobelts could be synthesized under a relatively low alkaline concentration (1 mol L-1 NaOH) and short duration (6 hours). At 3 mol L-1 HCl, rutile TiO2 nanorods were synthesized. Anatase TiO2 nanoparticles were obtained under pH values ranged between 2 to 13. FTIR analysis confirmed the phase change as the pH of the reacting medium increased from highly acidic to highly alkaline condition. The adsorption of methylene blue (MB) on the as-synthesized sodium titanate nanobelts 10 fitted well with the Langmuir monolayer model, with an adsorption capacity as high as 312.5 mg g-1. The kinetics of MB adsorption was found to be pseudo-second-order kinetic model. In brief, this study demonstrates a simple method to control the phase and morphology of titanium-based oxides. Excellent performance has been shown in the MB adsorption test by the sodium titanate nanostructures.